2021
DOI: 10.1177/26318318211017466
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Impacts of COVID-19 Pandemic on Lesbian, Gay, and Bisexual People Living in Portugal and Brazil—A Qualitative Study

Abstract: Introduction: Not many studies have been reported from Portugal or Brazil to date, reading the psychosocial impacts of COVID-19 on lesbian, gay, and bisexual (LGB) people, especially from a qualitative perspective. Materials and Methods: A convenience sample of 65 self-identified LGB individuals from Portugal and Brazil participated in this study. Thirty-two participants were from Portugal and 33 from Brazil. The average age was 34.48 years (standard deviation = 11.66), ranging from 19 to 67. We used an online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
0
7
0
3
Order By: Relevance
“…Theme 2: Loss of Social and Kinship Connection. The loss of social and kinship connection was reported across eight articles (Braksmajer & London, 2021;Gaspar et al, 2021;O'Brien et al, 2021;Pereira et al, 2021;Philpot et al, 2021;Quinn et al, 2021;Riggle et al, 2021;Westwood et al, 2021). This type of loss largely related to losses in the quality and quantity of friendships, LGBTQ+ people's Family of Choice, their Family of Origin and romantic or sexual partners (Wheat & Thacker, 2019).…”
Section: Inductive Thematic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Theme 2: Loss of Social and Kinship Connection. The loss of social and kinship connection was reported across eight articles (Braksmajer & London, 2021;Gaspar et al, 2021;O'Brien et al, 2021;Pereira et al, 2021;Philpot et al, 2021;Quinn et al, 2021;Riggle et al, 2021;Westwood et al, 2021). This type of loss largely related to losses in the quality and quantity of friendships, LGBTQ+ people's Family of Choice, their Family of Origin and romantic or sexual partners (Wheat & Thacker, 2019).…”
Section: Inductive Thematic Synthesismentioning
confidence: 99%
“…(p. 6). Pereira et al (2021) also reported how lesbian, gay and bisexual people in Portugal and Brazil felt vulnerable and experienced low self-esteem when they were not able to maintain their friendships during the pandemic and lockdown, owing to feelings of guilt as they thought they were responsible for the lost connection. The loneliness and social isolation that arose from lost social kinship connections were so intense in some instances that suicide was seen as the only way forward (O'Brien et al, 2021).…”
Section: Inductive Thematic Synthesismentioning
confidence: 99%
“…There are several examples, whether articulated or not, of intergenerational inequalities that are reproduced over time and have been enhanced by the COVID-19 pandemic (Carmo et al, 2020;Stok et al, 2021;O'Keefe et al, 2021;Cheshmehzangi, 2021), in a sort of vicious cycle, fostering the creation, within the same social groups, of new inequalities, such as the institutionalization of racism, sexism and the gender divide (Gugushvili, 2021;Farquharson & Thornton, 2020;Warren & Bordoloi, 2020;Wang et al, 2020;Lazonick, Moss, & Weitz, 2021;Bann et al, 2021;Pereira, Pedro, Mendes, Duarte, & Silva, 2021), ethnicity and disability (Burke, 2020;Katikireddi et al, 2021). This is the case of the studies on BAME (Black, Asian, and Minority Ethnicity) and social class (Burke, 2020), immigrants and disabilities (Warren & Bordoloi, 2020), ageism (Warren & Bordoloi, 2020), which often intersect with each other in a socio-historical perpetuation (Wang et al, 2020;Warren & Bordoloi, 2020), with profound influences on the individual's potential future social and economic path.…”
Section: Intergenerational Inequalities and Covid-19mentioning
confidence: 99%
“…Trata-se, portanto, de uma subnotificação favorecida pela falta de prioridade e comprometimento do governo bolsonarista de enfrentar a violência contra essa parcela da população. Além de o país registrar um dos maiores índices de crimes por homofobia, as minorias sexuais estão mais propensas a experiências de insegurança, hostilidade e violência, uma vez que a institucionalização e a aplicação das leis que visam coibir os crimes de homofobia ainda são insuficientes no Brasil (Pereira et al, 2021).…”
Section: Introductionunclassified